Bladder cancer-induced CVD mortality: Role of CAPG protein - Junwen Shen; Zhucheng Zhao; Zhaojun Li; Rongjiang Wang (PLoS ONE, 2026)
Objective Explore the causes and mechanisms of bladder cancer-induced Cardiovascular diseases (CVD) death. Method We acquired bladder cancer patient data from the SEER database to evaluate CVD death risk. Cross-WGCNA was employed to identify comorbidity genes linking bladder cancer and heart failure. Functional phenotypes of bladder cancer cell lines were analyzed using cell culture, transaction, CCK-8, and Transwell assays, while ELISA determined extracellular target protein concentrations. Myocardial cell function was assessed by examining cell proliferation, collagen I levels, and mitochondrial membrane potential. Result Our study, analyzing 140,760 bladder cancer patients from the SEER database, revealed that CVD is a major cause of death, increasing risk by 18%. Cross-WGCNA and Lasso regression identified SFRP1 and CAPG as key serum proteins linked to bladder cancer and heart failure. Regulating these proteins’ mRNA levels significantly impacts cancer proliferation, migration, and invasion. CAPG, in particular, suppresses myocardial cell function. We discovered SB525334 as a strong CAPG inhibitor in bladder cancer cells, potentially enhancing cisplatin’s effectiveness by targeting CAPG. Conclusion Bladder cancer patients face an elevated CVD death risk due to high CAPG protein expression, which can raise serum CAPG levels and harm cardiomyocytes.